The Analysis of Abnormal Stock Returns in LQ-45 Index during Covid-19 Pandemic - I Komang Agus Tresna Sukadarma; N W K Dewi; I K Parnata (Journal of Applied Sciences in Accounting, Finance, and Tax, 2021)
This research aimed: (1) to identify the average distinction of abnormal stock-return in LQ-45 during Covid-19 Pandemic around January-May 2020 in Indonesia, and (2) to identify the highest average abnormal stock-return during Covid-19 Pandemic around January-May 2020. The research sample used LQ-45 Share through purposive sampling method. Abnormal return denotes to the indicator used to measure the market reaction due to the particular event. Kolmogorov Smirnov and Kruskal Wallis test are used to assess the normality data and examine whether there was average distinction of abnormal stock-return in LQ-45 during Covid-19 Pandemic around January-May 2020 in Indonesia. The research finding represents that there is an average distinction of abnormal stock-return in LQ-45 during Covid-19 Pandemic in Indonesia. The most significant distinction shown on March 2020 which the average abnormal return value is 71.93, decreasing from February 2020 in average value of 102.43. Based on the data analysis, it is identified 17 companies with positive abnormal return whose highest average abnormal return during the pandemic around January-May 2020 is Barito Pacific Tbk (BRPT) company in value of 0.11399140.